PENGARUH STRUKTUR KEPEMILIKAN TERHADAP KEMUNGKINAN KESULITAN KEUANGAN PADA BURSA EFEK INDONESIA - Hastuti, Indra (Universitas Muhammadiyah Surakarta, 2014)
Financial distresses have strong relationships with the companyâ€™s bankruptcy. The ï¬nancial distress can be predicted by using information contained in the ï¬nancial statements and the companyâ€™s corporate governance mechanisms. The purpose of this study is to prove the effect of ownership structure, liquidity ratios, leverage ratios, activity ratios, and the size of the company to possible ï¬nancial distress of manufacturing companies in Indonesia Stock Exchange. Populations of this study are manufacturing companies in Indonesia Stock Exchange, which are published in the ï¬nancial statements from the years 2008-2012,samples of the researchÂ are 156 ï¬nancial. Data analysis uses a logistic regression .The results of this study indicate that managerial ownership signiï¬cantly inï¬‚uence of ï¬nancial distress. While institutional ownership does not signiï¬cantly inï¬‚uence of ï¬nancial distress. Liquidity ratios and activity ratios signiï¬cantly inï¬‚uence of ï¬nancial distress. While the leverage ratio and firm size had no signiï¬cant effect on the ï¬nancial distress. The results can be used for decision making corporate leaders and investors as well as potential investors to always attention Managerial ownership, liquidity ratio, and the ratio of the activity, because these three variables has a contribution in inï¬‚uencing the potential for ï¬nancial distress.